2008
DOI: 10.1210/en.2008-0352
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Up-Regulation of Prostaglandin E Synthase Expression in Breast Cancer Cells by 17β-Estradiol and Proinflammatory Cytokines

Abstract: Inflammatory mediators, such as cytokines and prostaglandins, play a fundamental role in estrogen-dependent breast cancer through their ability to up-regulate aromatase expression and subsequent local production of estrogens in the breast. To study the link between estrogens and inflammation further, we examined the regulation of prostaglandin E synthase (PTGES), a key enzyme in the production of prostaglandin E2. We found that 17beta-estradiol (E2) rapidly and robustly up-regulates PTGES mRNA and protein leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 51 publications
3
69
0
4
Order By: Relevance
“…However, there is an increasing amount of evidence that NF-kB activation occurs in a subset of endocrineresistant ER-positive tumors, and NF-kB activation in ER-positive tumors is associated with a more aggressive phenotype, which was caused by positive cross-talk between ER and the NF-kB pathway. For example, ER and p65 can cooperate to synergistically regulate expression of specific genes, such as PTGES, BIRC3, and ABCG2, which are important in regulation of invasiveness, survival, and chemoresistance of breast cancer cells (34,35). Meanwhile, it has been also reported that IKK-a could interact and phosphorylate ER, and then both proteins form a complex with SRC-3, leading to the phosphorylation of histone H3, and additional histone modifications that favor gene expression are recruited to the promoter of cyclin D1 and E2F1 (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an increasing amount of evidence that NF-kB activation occurs in a subset of endocrineresistant ER-positive tumors, and NF-kB activation in ER-positive tumors is associated with a more aggressive phenotype, which was caused by positive cross-talk between ER and the NF-kB pathway. For example, ER and p65 can cooperate to synergistically regulate expression of specific genes, such as PTGES, BIRC3, and ABCG2, which are important in regulation of invasiveness, survival, and chemoresistance of breast cancer cells (34,35). Meanwhile, it has been also reported that IKK-a could interact and phosphorylate ER, and then both proteins form a complex with SRC-3, leading to the phosphorylation of histone H3, and additional histone modifications that favor gene expression are recruited to the promoter of cyclin D1 and E2F1 (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Dans des lignées cellulaires de carcinome mammaire estrogéno-sensible, l'E2 par sa liaison au REα induit la transcription de la m-PGES pro-inflammatoire et entraîne une augmentation de la prolifération cellulaire (Frasor et al, 2003(Frasor et al, et 2008. Ces résultats sont en accord avec une diminution de la prolifération de ces cellules par l'ajout de 15d-PGJ2 dans les cultures cellulaires (Diers et al, 2010).…”
Section: Double Compétence Des Androgènes Et Modulation De La Productunclassified
“…Dans des lignées cancéreuses mammaires, il a été décrit que l'E2 régulerait la transcription de la m-PGES qui permet la formation de la PGE2 pro-inflammatoire (Frasor et al, 2003 ;Frasor et al, 2008). Cette prostaglandine favorise notamment la croissance tumorale et la survenue de métastases .…”
Section: L'effet Protecteur De L'e2 Chez Des Souris Présentant Une Enunclassified
See 2 more Smart Citations